2017
DOI: 10.1128/aem.00535-17
|View full text |Cite
|
Sign up to set email alerts
|

Transient Silencing of DNA Repair Genes Improves Targeted Gene Integration in the Filamentous Fungus Trichoderma reesei

Abstract: Trichoderma reesei is a filamentous fungus that is used worldwide to produce industrial enzymes. Industrial strains have traditionally been created though systematic strain improvement using mutagenesis and screening approaches. It is also desirable to specifically manipulate the genes of the organism to further improve and to modify the strain. Targeted integration in filamentous fungi is typically hampered by very low frequencies of homologous recombination. To address this limitation, we have developed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…However, Ku70 knockout strain may have higher instability than wild type. The alternative approaches to transiently downregulate ku70 can be considered to improve gene integration, which have been confirmed in Trichoderma reesei [42].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, Ku70 knockout strain may have higher instability than wild type. The alternative approaches to transiently downregulate ku70 can be considered to improve gene integration, which have been confirmed in Trichoderma reesei [42].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Construction of industrially useful filamentous fungi require efficient genetic tools to perform time-saving sequential manipulations or multiplex manipulations. It was previously reported that the efficiency of homologous DNA integration in the T. reesei mus53 deletion strain was up to 100% in some cases (Steiger et al, 2011; Chum et al, 2017). This inspired us to suppose that homologous DNA integration into multiple genomic loci may occur in QM9414Δ mus53 .…”
Section: Resultsmentioning
confidence: 99%
“…As a highly efficient producer of homologous and heterologous proteins, manipulation of the genome of T. reesei is supported by optimized tools like non-homologous end joining deficient (NHEJ) strains and genome wide deletion primer design ( Schuster et al, 2012 ), transient knock down of NHEJ ( Chum et al, 2017 ), or CRISPR/Cas9 mediated genome editing ( Liu et al, 2015 ). The genome of T. reesei is sequenced in high quality ( Martinez et al, 2008 ; Marie-Nelly et al, 2014 ; Li et al, 2017 ) and manually annotated ( Druzhinina et al, 2016 ; Schmoll et al, 2016 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%